HPV-Induced Field Cancerisation: Transformation of Adult Tissue Stem Cell Into Cancer Stem Cell - Olivero, Carlotta; Lanfredini, Simone; Borgogna, Cinzia; Gariglio, Marisa; Patel, Girish K. (Frontiers in Microbiology, 2018)
Field cancerisation was originally described as a basis for multiple head and neck squamous cell carcinoma (HNSCC) and is a pre-malignant phenomenon that is frequently attributable to oncogenic human papillomavirus (HPV) infection. Our work on β-HPV-induced cutaneous SCC identified a novel Lrig1+ hair follicle junctional zone keratinocyte stem cell population as the basis for field cancerisation. Herein, we describe the ability for HPV to infect adult tissue stem cells in order to establish persistent infection and induce their proliferation and displacement resulting in field cancerisation. By review of the HPV literature, we reveal how this mechanism is conserved as the basis of field cancerisation across many tissues. New insights have identified the capacity for HPV early region genes to dysregulate adult tissue stem cell self-renewal pathways ensuring that the expanded population preserve its stem cell characteristics beyond the stem cell niche. HPV-infected cells acquire additional transforming mutations that can give rise to intraepithelial neoplasia, from environmental factors such as sunlight or tobacco induced mutations in skin and oral cavity respectively. With establishment of intraepithelial neoplasia, HPV viral replication is sacrificed with loss of the episome, and the tissue is predisposed to multiple cancer stem cell-driven carcinomas.